Association of cholesterol with hepatorenal markers and quality of life in diabetic patients before and after magnesium and potassium supplements - Sidra Khalid; Shahid Bashir; Shahnai Basharat; Riffat Mehboob; Tehreem Anwar; Mariam Hashim; Raha Orfali; Syed Arif Hussain; Rafiulla Gilkaramenthi; Ebtesam Abdulrahman Jibreel; Syed Mohammed Basheeruddin Asdaq; Shakira Ghazanfar (Saudi Pharmaceutical Journal, 2023)
Background: Magnesium and potassium are two critical minerals that have been linked to the treatment of diabetes and its consequences. A lack of magnesium has been linked to insulin resistance and diabetes, whereas potassium has been found to promote insulin sensitivity and glucose metabolism. The study aimed to determine the relationship between cholesterol, liver and kidney markers, and quality of life in diabetic patients before and after magnesium and potassium supplementation. Methods: It was a single-blind randomized controlled study at Lahore Garrison University and Lahore Medical Research Centre (LMRC). The study included 200 diabetes participants. Four groups were made based on supplements. Blood samples of all diabetes patients were obtained to assess their quality of life before and after using Mg + and K + supplements, as well as the association between cholesterol, liver, and kidney markers. Results: The participants' average age was 51.0 ± 11.08. 139 (69.5 %) of the 200 participants were female, whereas 26 (30.5 %) were male. There was no correlation between the quality of life measure and the patients' cholesterol levels before and after the magnesium and potassium supplementation. Furthermore, the kidney and liver indicators were not dependent on the diabetes individuals' cholesterol levels. Conclusions: The study concluded that none of the four groups noticed a significant effect of magnesium and potassium therapies on the patient's quality of life or cholesterol levels. However, more research is needed to determine if liver and kidney problems are linked to cholesterol levels before and after medication, as the current study found no significant correlation between the two parameters.